2010
DOI: 10.1063/1.3369434
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation effect by nanotexturing InGaN/GaN multiple quantum well

Abstract: The relaxation of lattice-mismatched strain by deep postetching was systematically investigated for InGaN/GaN multiple quantum wells ͑MQWs͒. A planar heterojunction wafer, which included an In 0.21 Ga 0.79 N ͑3.2 nm͒/GaN ͑14.8 nm͒ MQW, was etched by inductively coupled plasma dry etching, to fabricate high-density nanopillar, nanostripe, and nanohole arrays. The etching depth was 570 nm for all nanostructures. The diameter of the nanopillars was varied from 50 to 300 nm, then the mesa stripe width of the nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 39 publications
5
67
0
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12] The fabrication method has typically involved "top-down" patterning by etching an initially planar epitaxial structure containing InGaN/GaN QWs, although studies of directly grown nano-columnar structures have also been reported. 12 Correlations between spectroscopic results and numerical simulations of strain relaxation in the QWs were included in the reports by Yu et al 9 and Kawakami et al 10 The authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] The fabrication method has typically involved "top-down" patterning by etching an initially planar epitaxial structure containing InGaN/GaN QWs, although studies of directly grown nano-columnar structures have also been reported. 12 Correlations between spectroscopic results and numerical simulations of strain relaxation in the QWs were included in the reports by Yu et al 9 and Kawakami et al 10 The authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Ramesh et al 119 demonstrated that for the etched GaN nanoLED arrays the emission wavelength had a blueshift from 510 nm for an as-grown layer to 459 nm for top-down GaN nanoLED with a diameter of 51 nm at 300 K (shown in Fig. 23 left).…”
Section: Gan Nanoledmentioning
confidence: 99%
“…Unfortunately, a large, strain-induced electric field in III-N heterostructures often severely suppresses the oscillator strength of the exciton and, hence, the radiative decay rate and the internal quantum efficiency (IQE). Since strain is relaxed near free surfaces, nanodisks (NDs) in nanowires, which has a large surfaceto-volume ratio, have been widely considered as a promising solution for improving the IQE of InGaN/GaN photonic devices [4][5][6][7][8][9][10][11] . The accompanying improvement in the radiative decay rate is also important for realizing ultrafast singlephoton sources using InGaN/GaN QDs 3,12 .…”
mentioning
confidence: 99%